The Development and Challenges of Water Markets for Irrigation: The case of New South Wa1es in Australia - KINOSHITA, Yukio; Lin, CRASE (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 2006)
The subject of this research is to clarify current situations and challenges of water markets for irrigation mainly in the State of New South Wales in Australia. This research takes an approach with observation of the actual condition towards the subject. The background of the development of water trade has been examined to be proved to be a political factor, a natural factor, and an institutional factor. The market structure involving water trade for irrigation in the Murray Valley has been examined to clarify some characteristics of water market such as features of temporary trade and thin market of permanent trade. The conditions for successful water market, devaluation loss on water entitlement as asset, and consistency with the policy towards water market have been also discussed to add some new arguable points for the development of water market.